Psychometric testing of the facilitative student–patient relationship scale within six EUROPEAN countries - Suikkala Arja; Koskinen Sanna; Brasaitė-Abromė Indrė; Fuster-Linares Pilar; Lehwaldt Daniela; Leino-Kilpi Helena; Meyer Gabriele; Sveinsdóttir Herdís; Katajisto Jouko; ProCompNurse Consortium (Wiley, 2023)
Aim: The aim of the study was to test the psychometric properties of the Facilitative Student-Patient Relationship (FSPR) Scale in clinical practicum in hospital settings within six European countries.
Design: A multi-country, cross-sectional survey design was applied.
Methods: A convenience sample of graduating nursing students (N = 1,796) completed the FSPR Scale. Psychometric testing was carried out through explorative factor analysis and confirmatory factor analysis. Internal consistency was assessed using Cronbach's alpha.
Results: Both validity and reliability of the scale were confirmed. The explorative factor analysis yielded a two-factor construct explaining 47.7% of the total variance, identifying two sub-scales: caring relationship and learning relationship. Confirmatory factor analysis confirmed the two-factor structure. The Cronbach alpha coefficients (0.8-0.9) indicated acceptable reliability of the scale.
Keywords: clinical; education; nursing; psychometric; student-patient relationship; students; surveys.